Survey of flies (order: diptera) of Medical and Veterinary importance infesting livestock in Maiduguri, Borno state, Nigeria - Abubakar, B.A.; Falmata, K.; ThankGod, O.E.; Abdulmalik, A.; Ali, M. (Journal of Scientific Agriculture, 2018)
An entomological survey of dipterous flies was conducted between January and March 2017 to investigate the distribution, relative abundance and monthly distribution of vectors flies of livestock in Maiduguri metropolis, Borno state. A total of 5192 flies were caught from four (4) different locations within Maiduguri using biconical trap and aerial sweeping hand net. Flies were collected and identified using standard taxonomy keys. Musca domestica was considered most prevalent 4346 (73.71%) while Hippobosca equina 4(0.08%) was the least. Others are Stomoxys calcitrans 6(0.12%), Tabanus sp. 5(0.10%) and Lucilia cuprina 831(16%). The number of female flies caught in the study campaign was higher 3086(59.44%) than that of male flies 2106(40.56%). The total number of non-haematophagous flies caught was much higher 5177(59.42%) than that of haematophagous flies 15(0.29%). Furthermore, of the four different sampling area; Livestock market has the higher number of catches 3432 (66.10%), Animal science poultry house 920(17.72%), Large animal clinic 462 (8.09%) and Gidan doki had the least catches 378(7.28%). In addition, the number of adult flies caught was higher 2922 (56.28%) than immature flies 2270 (43.72%). Results from the monthly distribution shows that January had the least 1473 (28.37%) followed by February 1664 (32.05%) and March 2047 (39.43%) had the highest number of catches. The veterinary and medical importance of the findings is discussed.